التسويق الالكتروني ودوره في صناعة السياحة - زقب, هشام; عسيلة, عبد الفتاح; محده, ابراهيم (University of eloued جامعة الوادي, 2019)
هدفت هذه الدراسة إلى تبيان أهمية التسويق الالكتروني ودوره في صناعة السياحة في ظل التغيرات الجذرية الحاصلة في البيئة التسويقية، دفعت العديد من الهياكل السياحية والفندقية إلى إعادة التفكير في الدور الأساسي للتسويق، ونتيجة للمنافسة العالمية أصبح من الضروري على عالم الأعمال إن يسعى إلى طرق أكثر فاعلية نحو دراسة التسويق، و ابتكار أساليب و طرق أكثر فعالية و العمل على استقطاب الزبائن وتنشيط المعاملات والتبادلات في ظل التكنولوجيا الرقمية ، فكان لابد من استخدام أسلوب التسويق الالكتروني حيث يساهم هذا الأسلوب في تعزيز الخطط التسويقية لطرح المنتجات في الأسواق وخلق فضاء جديد ونظرة أخرى للسياحة . لتحقيق أهداف الدراسة والإجابة على تساؤلاتها، اعتمدنا على المعلومات والبيانات المتعلقة بالموضوع وذات الصلة بهدف تطبيق المفاهيم النظرية للدراسة المأخوذة من المركب السياحي. This study aimed to demonstrate the importance of electronic marketing and its role in the tourism industry in light of the drastic changes taking place in the marketing environment, which prompted many tourism and hotel structures to rethink the essential role of marketing. As a result of global competition it is necessary for the business world to seek more effective ways Towards the study of marketing, the development of methods and methods more effective and work to attract customers and the activation of transactions and exchanges under the digital technology, was to use the method of electronic marketing, which contributes to the promotion of marketing plans to put products in Markets and create a new space and another look for tourism. To achieve the objectives of the study and answer its questions, we relied on the relevant information and data related to the purpose of applying the theoretical concepts of the study taken from the tourist complex.
مذكرة ماستر تخصص تسويق فندقي وسياحي
Keywords: التسويق الالكتروني ،صناعة السياحة ،طلب سياحي ،جذب سياحي; E-marketing, tourism industry, tourism application, tourist attraction